Reduction in Nonabstinent WHO Drinking Risk Levels and Change in Risk for Liver Disease and Positive AUDIT‐C Scores: Prospective 3‐Year Follow‐Up Results in the U.S. General Population. (3rd October 2018) - Knox, Justin; Wall, Melanie; Witkiewitz, Katie; Kranzler, Henry R.; Falk, Daniel; Litten, Raye; Mann, Karl; O'Malley, Stephanie S.; Scodes, Jennifer; Anton, Raymond; Hasin, Deborah S.; ,
Abstract : Background: Abstinence is often the treatment aim for alcohol use disorders (AUD), but this may deter individuals who prefer drinking reduction goals from entering treatment, and be an overly restrictive end point in alcohol clinical trials. Nonabstinent drinking reductions that predict improvement in how individuals feel or function may be useful clinical trial outcomes, for example, reductions in the 4‐category World Health Organization (WHO) drinking risk levels. To investigate the clinical relevance of these reductions, we examined their relationship with 2 outcomes of interest to medical providers: liver disease, and positive scores on an alcohol screening measure. Methods: Current drinkers in a U.S. national survey ( n  = 21, 925) were interviewed in 2001 to 2002 (Wave 1) and re‐interviewed 3 years later (Wave 2). WHO drinking risk levels, liver disease, and the Alcohol Use Disorders Identification Test‐Consumption (AUDIT‐C) were assessed at both waves. Adjusted odds ratios (aORs) were used to indicate the association of change in WHO drinking risk levels with Wave 2 liver disease and AUDIT‐C scores. Results: Wave 1 very‐high‐risk drinkers who reduced 1, 2, or 3 WHO drinking risk levels had significantly lower odds of Wave 2 liver disease (aORs = 0.34, 0.23, 0.17) and positive AUDIT‐C scores (aORs = 0.27, 0.09, 0.03). Wave 1 high‐risk drinkers who reduced 1 or 2 WHO risk levels had significantly lower odds of positive AUDIT‐C scores (aORs = 0.61, 0.25). Adjusting for alcohol dependence or AUDIT‐C scoring variations did not affect results. Conclusions: In the highest‐risk drinkers, reductions in WHO drinking risk levels predicted lower likelihood of liver disease and positive AUDIT‐C scores. Results add to findings that reductions in the 4‐category WHO drinking risk levels are a meaningful indicator of how individuals feel and function, and could serve as nonabstinent end points in clinical trials. Results also connect the WHO risk drinking levels to commonly used alcohol screening questions, which may be more familiar to healthcare providers. Abstract : If associated with benefit, non‐abstinent reductions in heavy drinking may provide a more sensitive clinical trial outcome measure than abstinence, and help engage individuals in treatment who are uninterested in an abstinence goal. In the general population, non‐abstinent reductions in the 4‐category WHO drinking risk levels predicted lower risk of liver disease and positive alcohol screening scores at 3‐year follow‐up. Results add to literature supporting non‐abstinent reductions as useful goals in treatment, and as valid AUD clinical trial outcome indicators